Implementation Of MAUT Method for Making Website-based Tourism Recommendations in Yogyakarta based on Maps Location - Nuraminudin, M.; Dewi, Melany Mustika; Dahlan, Akhmad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The significance of the tourism sector in contributing to the economy of the Special Region of Yogyakarta, which is a major destination with millions of tourists every year. The rapid growth of tourism demands the integration of information technology, especially in the development of recommendation systems, to improve visitor experience and satisfaction and support sustainable destination management. The main problem faced is the need to develop a recommendation system that is able to provide optimal suggestions for tourist locations and accommodations, considering various attributes such as price, facilities, location, and user personal preferences. The problem-solving approach taken in this study is the application of the Multi-Attribute Utility Theory (MAUT) Method. The research steps involve identifying problems, needs, and key attributes, collecting tourist location and accommodation data through Google Maps and Google Business Data. Furthermore, the raw data is subjected to processing and pre-processing before the MAUT model is developed. This model is implemented into a web-based application which is then tested using blackbox testing to determine whether the system is running properly. With the hope of creating a smart and sustainable tourism ecosystem, this study is innovative in using MAUT to improve the quality of recommendations in the Yogyakarta tourism industry.